Revolutionizing Islamic Education through Curriculum Innovation: Insights from Izzuddin Integrated School, Indonesia - Lies Nur Intan; Muhammad Sirozi; Karoma (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Basic Education Curriculum Innovation: A Case Study of the Curriculum of Islamic Religious Education Subjects at Izzuddin Integrated Islamic Elementary School Palembang. The Islamic Religious Education Curriculum at Izzuddin Integrated Islamic Elementary School Palembang has undergone innovations to improve the quality of religious learning. This innovation includes aspects of curriculum structure, materials, and learning methods, with the aim of strengthening students' religious competence in accordance with the times. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, and analysis of documents, involving internal and external stakeholders, such as principals, teachers, and parents of students. The results of the study show that the innovation of the Islamic Religious Education curriculum at Izzuddin Integrated Islamic Elementary School includes the separation of Qur'an-based classes and regular classes, as well as the addition of special subjects such as Takhsin, Tahfidz, Fashohah, and Muroja'ah. The learning process is supported by a project-based interactive method that adjusts lesson hours and creates a conducive learning environment. Stakeholders responded positively to this innovation, appreciating its impact on improving students' academic skills and spiritual character. Overall, this curriculum innovation makes an extraordinary contribution to the learning of Islamic Religious Education by integrating  the Tahfidz Qur'an program  structurally and based on strong Islamic values